ROLE OF MEDIATION IN FACILITATING ACCESS TO JUSTICE IN ITS TRUE ESSENCE: A CRITICAL ANALYSIS - Mishra, Ashutosh; Kharat, Madhuri; Acharya, Ashutosh; Sonawane, Ajay; Shukla, Shruti; Maurya, Suraj Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The concept of justice is not novel, and so is Mediation. Since the inception of human interactions, disagreements and disputes have been a part of living. When Indian legal System was being formed, it was designed following the adversarial system that seem to favour the strong party and follow the already written law points with little or no room for creative solutions. Also, there are several provisions and arrangements made to extend the access of legal corridors to the underprivileged and left out segments of the society; but this does not ensure that justice has been realised in its true essence. Mere access to legal means, is not access to justice too. This is where Mediation as a means of alternative dispute resolution steps in and creates a comfortable, private, inexpensive and self- determined environment for both the parties at dispute. This paper examines what is true justice and what our constitution makers had in mind in relation to notion of justice when they attempted to give us the related rights. Justifying the stance with real life scenarios and cases, the paper also elucidates how Mediation can help parties achieve justice in its real sense and not just literal or technical.